ANALYSIS OF MANAGEMENT EFFORTS IN SHAPING SAFETY CULTURE IN X HOSPITAL SEMARANG - Hestyani Kelananingrum; Antono Suryoputro; Bagoes Widjanarko (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Patient safety is the essence of health service quality. Hospitals are a combination of several elements that together produce a high-risk situation. Safety culture should be the core in hospital organization. From the data obtained there are still incidents of safety of patients in hospital X Semarang and there has been no trend decrease in the incidence of meaningful incidents over time. This research aims to determine the cultural overview of safety and how the management efforts influence in shaping the safety culture of hospital X Semarang. This type of research is quantitative analytic with survey method that analyzes management efforts in shaping safety culture in hospital X Semarang. Research conducted in January-March 2020. Data collection techniques using a questionnaire adapted from the American College of Healthcare Executives in 2017 and a description of safety culture were acquired by collecting data from a Patient safety culture questionnaire adopted from the Hospital Survey on Patient Safety Culture questionnaire published by The Agency for Healthcare Research and Quality (AHRQ) in 2004. Number of respondents as many as 220 people selected in proportionate stratified random sampling. The results showed that the safety culture at hospital X showed a positive response in the organizational learning dimension and continuous improvement (90.15%), the dimension of cooperation in units (81.82%) and dimension of management support to patient safety efforts (80.45%). The other dimension of safety culture has a negative response (< 75%). Management efforts that include the determination of vision, trust values, respect and inclusion, selection, development and management engagement, leadership development that prioritizes safety, just culture, expectations of organizational behaviour as well as assumptions, values and artifacts related to safety culture have an influence in the establishment of safety culture in hospital X Semarang.Keyword: Safety Culture, management efforts